A new fate mapping system reveals context-dependent random or clonal expansion of microglia - Tay, Tuan Leng; Mai, Dominic; Dautzenberg, Jana; Fernandez-Klett, Francisco; Lin, Gen; Sagar; Datta, Moumita; Drougard, Anne; Stempfl, Thomas; Ardura-Fabregat, Alberto; Staszewski, Ori; Margineanu, Anca; et al. (Nature Neuroscience, 2017)
Microglia constitute a highly specialized network of tissue-resident immune cells that is important for the control of tissue homeostasis and the resolution of diseases of the CNS. Little is known about how their spatial distribution is established and maintained in vivo. Here we establish a new multicolor fluorescence fate mapping system to monitor microglial dynamics during steady state and disease. Our findings suggest that microglia establish a dense network with regional differences, and the high regional turnover rates found challenge the universal concept of microglial longevity. Microglial self-renewal under steady state conditions constitutes a stochastic process. During pathology this randomness shifts to selected clonal microglial expansion. In the resolution phase, excess disease-associated microglia are removed by a dual mechanism of cell egress and apoptosis to re-establish the stable microglial network. This study unravels the dynamic yet discrete self-organization of mature microglia in the healthy and diseased CNS.
CRIS-Team Scopus Importer:2023-03-23